2001
DOI: 10.1111/0021-8294.00088
|View full text |Cite
|
Sign up to set email alerts
|

Tolerant (In)civility? A Longitudinal Analysis of White Conservative Protestants’ Willingness to Grant Civil Liberties

Abstract: Past research has found conservative Protestants to be less willing than most Americans to grant civil liberties to unpopular groups. In light of evidence of high and growing civility by Smith (2000) and Hunter (1984), there is good reason to believe that conservative Protestants are becoming less distinctive with regard to granting civil freedoms. We update and expand previous research on conservative Protestants and civil liberties by examining the civil liberties measures in the General Social Survey over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 28 publications
5
47
0
Order By: Relevance
“…First, one could argue that these evangelical Protestants provide us with a ''most-difficult case.'' Survey research consistently finds white evangelicals to be less tolerant of those with opposing political views than are other citizens (Beatty and Walter 1984;Wilcox and Jelen 1990;Reimer and Park 2001; but see Eisenstein 2008). 4 The second reason I restrict my sample to evangelical Protestants participating in the Christian Right social movement is to test for particular cue-giver effects unique to this population offering us a ''real world'' scenario while contributing to the literature concerned with religio-political mobilization.…”
Section: Data and Research Designmentioning
confidence: 99%
“…First, one could argue that these evangelical Protestants provide us with a ''most-difficult case.'' Survey research consistently finds white evangelicals to be less tolerant of those with opposing political views than are other citizens (Beatty and Walter 1984;Wilcox and Jelen 1990;Reimer and Park 2001; but see Eisenstein 2008). 4 The second reason I restrict my sample to evangelical Protestants participating in the Christian Right social movement is to test for particular cue-giver effects unique to this population offering us a ''real world'' scenario while contributing to the literature concerned with religio-political mobilization.…”
Section: Data and Research Designmentioning
confidence: 99%
“…Thus, a potentially sensitive, but important, question for student consideration in social science courses would be what psychological characteristics and sociopolitical perspectives led evangelicals to prefer one candidate over the other. Fortunately, recent research has addressed the association between religious conservatism and a variety of psychological characteristics (e.g., authoritarianism and prejudice) and sociopolitical values, including militarism and respect for civil liberties (Altemeyer, 2003;Altemeyer & Hunsberger, 1992;Reimer & Park, 2001;Williams, Bliss, & McCallum, in press). Such research could be introduced into a class discussion without the instructor's attaching a value judgment to the documented empirical relationships (i.e., the findings could be examined without the instructor's using them to support or attack conservative religious beliefs).…”
Section: Instructor Role In Discussion Of Controversial Issuesmentioning
confidence: 99%
“…The concept of literalists being unique from other responses has been well established in the literature with other research indicating that literalism signals a different theological outlook than those who hold a less strict view (Wilcox and Jelen 1990;Reimer and Park 2001;Eisenstein 2006;Froese, Bader, and Smith 2008). The GSS offers four possible responses to the question that summarized are: the Bible should be taken literally, the Bible is inspired but should not be taken literally, the Bible is a book of fables, and an "other" response (for full question wording see the online Appendix).…”
Section: Methodsmentioning
confidence: 98%
“…A dummy variable for gender has been included as previous research has indicated that females show higher levels of tolerance (Gibson 1992;Froese, Bader, and Smith 2008). Additional controls include age (Hunter 1992;Wilson 1994), education (McClosky andBrill 1983;Nunn, Crockett, and Williams 1978;Bobo and Licari, 1989), Republican ideology (Wilcox and Jelen 1990;Reimer and Park 2001) as well as using an occupational prestige score as a proxy for income as nearly half of the respondents refused to disclose their income (Eisenstein 2006;Froese, Bader, and Smith 2008). Additionally, a control for region of the country has been included that separates those from the American south from the rest of the sample, this has shown to be an important control in previous work (Ellison and Sherkat 1993).…”
Section: Methodsmentioning
confidence: 99%